Digital technologies in music education. Using Digital Audio Workstations (DAW) with Project-Based Learning (PBL) - María Elena Cuenca-Rodríguez; Ignacio Pascual-Moltó; Raquel Pastor-Prada (Revista Latinoamericana de Tecnología Educativa)
BandLab and Walk Band are two mobile and web-based applications that let users create and record their own songs, providing them with a variety of virtual instruments, samples, loops and drum machines. These applications can be used as educational tools to encourage musical learning and creativity in secondary and higher education students. This article discusses the advantages and challenges of using these applications in education and offers some recommendations for their pedagogical use. The objective is to show how BandLab and Walk Band can contribute to the development of musical, artistic and digital proficiency in students as well as create collaborative learning communities. A literature review on previous uses of multitrack sequencers is also done, and some examples of didactic proposals on music creation and musical arrangements are offered on how to integrate these applications in the music curriculum in secondary education and in interdisciplinary projects in higher education. Finally, some challenges and opportunities are presented for research and educational innovation through the use of these technologies in the field of music creation.